تأثير المعالجات الحرارية على خواص التعب للمعادن - محمد زهرة; نيرودا بركات; يوسف ديب (Tishreen University, 2019)
This research aims at exploring the effects of heat treatments on fatigue properties of important metal alloys in the industry (low-carbon steels and leaded brass). Foundry-Master spectrometer was used to know the contents of the two alloys. Specimens of the two alloys were made by a CNC according to ASTM for those two alloys for both the tensile and fatigue tests. Tensile tests were done using a universal testing machine IBMU4 -1000 and fatigue tests on an SM1090 fatigue testing machine. Heat treatments were undertaken on both sets of samples of the two alloys. Results of tensile and fatigue tests were compared before and after heat treatments and we found an improvement of fatigue properties for both alloys although there was no clear value for fatigue limit for leaded brass but fatigue rate for the steel sample was obvious and it increased from 0.508 to 0.598 after heat treatments. يهدف هذا البحث إلى دراسة تأثير المعالجات الحرارية على خواص التعب لبعض السبائك المعدنية الهامة في الصناعة (الفولاذ المنخفض الكربون - النحاس الأصفر) حيث تم إجراء اختبار التحليل الطيفي لكلا السبيكتين على جهاز Foundry-Master لمعرفة النسب المئوية للعناصر الداخلة بتركيب كلا السبيكتين كما تم تصنيع العينات الخاصة باختبار التعب على آلة CNC  حسب المواصفات القياسية ASTM  لعينات التعب وإجراء المعالجة الحرارية الخاصة بكل سبيكة على حدا، كما تم تصنيع بعض العينات الخاصة باختبار الشد حسب المواصفات القياسية (DIN 50125) لعينات الشد، ثم تم إجراء مقارنة بين نتائج اختبارات الشد على آلة الاختبارات العامة IBMU4 -1000  قبل وبعد المعالجة الحرارية وكذلك مقارنة نتائج اختبارات التعب على آلة التعب الدورانية SM1090  قبل وبعد المعالجات الحرارية، وأظهرت النتائج تحسناً واضحاً في خواص التعب لكلا المعدنين بعد المعالجة الحرارية بالرغم من عدم وجود حد تعب محدد وواضح لسبيكة النحاس الأصفر بينما كان تحسن معدل التعب للفولاذ المذكور مميزاً حيث كانت قيمته 0.508 قبل المعالجة الحرارية وأصبحت 0.598 بعدها.